2022
DOI: 10.3390/molecules27238601
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the LC–MS/MS Method for Determination of 130 Natural and Synthetic Cannabinoids in Cannabis Oil

Abstract: Dietary supplements are widely available products used by millions of people around the world. Unfortunately, the procedure of adding pharmaceutical and psychoactive substances has recently been observed, in order to increase the effectiveness of supplements in the form of hemp oils. For this reason, it is extremely important to develop analytical methods for the detection of substances prohibited in dietary supplements and food products. In the present study, using the LC–MS/MS technique, an innovative method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…[1][2][3][4] There are several studies on the HPLC-based analysis of cannabis oil or CBD (5)-rich oil available in the literature for the period covered in this article. 44,97,[102][103][104][105][106][107][108][109][110][111][112] However, the analysis of cannabis oil using UHPL or UPLC has been limited to a few studies reported in the literature (Table 2).…”
Section: Hplc and Uplc (Or Uhplc) Analysis Of Cannabis Consumer Productsmentioning
confidence: 99%
See 4 more Smart Citations
“…[1][2][3][4] There are several studies on the HPLC-based analysis of cannabis oil or CBD (5)-rich oil available in the literature for the period covered in this article. 44,97,[102][103][104][105][106][107][108][109][110][111][112] However, the analysis of cannabis oil using UHPL or UPLC has been limited to a few studies reported in the literature (Table 2).…”
Section: Hplc and Uplc (Or Uhplc) Analysis Of Cannabis Consumer Productsmentioning
confidence: 99%
“…Analakkattillam et al 108 reported an isocratic HPLC run (20 min) for the detection of CBD (5) and Δ 9 -THC (14) in cannabis oil-infused products, while a gradient elution was conducted with water and MeOH, both containing 0.1% HCOOH and 2 mM ammonium formate, to identify CBC (1), CBD (5), CBDA (6), CBDVA (18), CBG (8), CBGA (9), cannabigerovarinic acid (CGBVA), CBN (10), cannabivarin (CBV), Δ 9 -THC ( 14), Δ 9 -THCA (15), THCV (16), and THCVA (17) in cannabis oil and oil-containing capsules using an ESI-MS detector operated in positive ion mode. 109 The use of the isocratic mobile phase in HPLC-UV (or PDA) analysis of CBD-oil has been quite popular as the analysis generally targets the detection of CBD ( 5) and a few other cannabinoids. 44,97,111 Li et al 111 have recently reported the analysis of CBD ( 5) full spectrum oil revealing the presence of CBD ( 5), CBDA (6), CBDV (18) (5), CBDA (6), CBN (10), Δ 9 -THC ( 14), and Δ 9 -THCA (15) in the samples using a simple UV detector.…”
Section: Hplc and Uplc (Or Uhplc) Analysis Of Cannabis Consumer Productsmentioning
confidence: 99%
See 3 more Smart Citations